2017
DOI: 10.3390/ma10050480
|View full text |Cite
|
Sign up to set email alerts
|

Practical Cluster Models for a Layered β-NiOOH Material

Abstract: Due to the high oxygen evolution reaction (OER) activity, stability, and abundance of NiOx materials, they are found to be promising catalysts, competitive with expensive metal oxides such as IrO2 and RuO2. From a theoretical point of view, studies reported in the literature so far are mostly based on density functional theory using periodic slab models for the bulk and surface of β-NiOOH, one of the active NiOx phases. However, cluster models are a valid method to investigate many aspects about structure, cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Previous studies have reported that β-NiOOH is more reactive to OER than β-Ni­(OH) 2 phase. In our calculations regarding the catalysis of OER, we removed half of the hydrogen atoms to transform the β-Ni­(OH) 2 into β-NiOOH and optimized the heterostructure. By that, we consider that in the work of Jia et al, local phase transformation in the nickel layer has occurred during the electrochemical cycle so that OER proceeds.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that β-NiOOH is more reactive to OER than β-Ni­(OH) 2 phase. In our calculations regarding the catalysis of OER, we removed half of the hydrogen atoms to transform the β-Ni­(OH) 2 into β-NiOOH and optimized the heterostructure. By that, we consider that in the work of Jia et al, local phase transformation in the nickel layer has occurred during the electrochemical cycle so that OER proceeds.…”
Section: Resultsmentioning
confidence: 99%
“…Investigations based on a cluster model approach can be advantageous over periodic boundary condition (PBC) methods because they enable the use of hybrid functionals at a lower computational cost, and, therefore, a highly accurate description of electronic properties. Moreover, cluster approaches are more appropriate for studying charged systems, thanks to the ability to add/subtract a charge carrier without suffering from interactions with similar charge carriers due to periodic boundary conditions. , Due to their reduced size, cluster approaches can be used to investigate complex reaction mechanisms, allowing for the interception of all the involved stationary points, including the more complex transition states. However, PBC calculations allow for modeling more extended surfaces and provide an accurate description of the structural properties of the surface and molecular adsorbates. The complementarity of the two computational methods can therefore lead to an in-depth understanding of the structure–property relationship …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cluster approaches are more appropriate for studying charged systems, thanks to the ability to add/subtract a charge carrier without suffering from interactions with similar charge carriers due to periodic boundary conditions. 28,29 Due to their reduced size, cluster approaches can be used to investigate complex reaction mechanisms, allowing for the interception of all the involved stationary points, including the more complex transition states. 30−32 However, PBC calculations allow for modeling more extended surfaces and provide an accurate description of the structural properties of the surface and molecular adsorbates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41][42] Motivated by these promising results, in a preliminary work, [24] we have investigated the photocatalytic activity of the undoped GaN and GaN doped with one single Mg atom, along with the CO 2 reduction to methanol. The DFT investigation was carried out using a cluster model approach, that has some advantages over periodic boundary condition (PBC) calculations such us the utilization of hybrid functionals, [43][44][45] and the investigation of complex reaction mechanism, [46,47] at lower computational cost than periodic boundary condition (PBC) calculations. However, cluster model approaches do not allow for the investigation of extended surfaces and heterojunctions, which can be more conveniently performed by means of PBC calculations.…”
Section: Introductionmentioning
confidence: 99%